Embodiments and frictions of statehood in transnational criminal justice - Stambøl, Eva Magdalena (Theoretical criminology, 2021)
Outside of criminology, dominant conceptions of postcolonial statehood in the Global South as ‘fragile’ or ‘failed’ have long been criticized. In criminology, however, the theoretical outcomes of this critique have been scarce. In this article we therefore ask how ideals and practices of transnational criminal justice are informed by and productive of specific (Global North) conceptions of statehood. Exploring encounters between transnational and local criminal justice in the context of international state-building in Mali and Liberia, we observe frictions in which statehood divergences and global hierarchies become apparent. Through penal aid, we argue, a particular kind of penal statehood is produced wherein the options of how to perform penality are increasingly limited by the embeddedness in global power asymmetries.